Realization of multiphase sinusoidal oscillator using CDBAs - Klahan, K.; Tangsrirat, W.; Surakampontorn, W. (My University, 2004)
A multiphase sinusoidal oscillator with the employment of current differencing buffered amplifiers (CDBAs) as an active element is presented in this paper. The proposed oscillator circuit is composed of n cascaded lossy integrators and n inverters, which can generate 2n different phase sinusoidal voltage (180°/n and 180°/n+180°). The oscillation frequency can be wide range adjusted, approximately 3 decades, through the value of active elements. Experimental results obtained using the AD844 ICs are given to confirm the theoretical analysis. © 2004 IEEE.